An insight - A statistical investigation of consolidated bioprocessing of Allium ascalonicum leaves to ethanol using Hangateiclostridium thermocellum KSMK1203 and synthetic consortium. (March 2022) - Kavitha, S.; Gajendran, T.; Saranya, K.; Selvakumar, P.; Manivasagan, V.; Jeevitha, S.
Abstract: Bioethanol can be produced by cellulolytic and ethanogenic bacterial species could efficiently degrade lignocelluloses and have potential for biofuels production through consolidated bioprocessing (CBP). In this study, on-site cellulase production followed by saccharification and fermentation of pre-treated Allium ascalonicum leaves to bioethanol in a single reactor using Hangateiclostridium thermocellum KSMK1203 and consortium of Cellulomonas fimi MTCC 24 and Zymomonas mobilis MTCC 92. A. ascalonicum leaf pre-treatment with different alkalis and different pre-treatment conditions such as alkali dosage and time for proficient removal of hemicellulose and cellulose recovery was optimized using RSM method with the maximum hemicellulose removal of 85.25%. The essential medium components were screened through PBD and further optimized using RSM method for H. thermocellum KSMK1203 and the consortium for maximized bioethanol yield. Hence, this study proposed that wild-type H. thermocellum KSMK1203 strain and consortium could be used for cellulase secretion and simultaneous bioethanol conversion. Graphical abstract: Image 1 Highlights: Allium ascalonicum leaf biomass was used for bioethanol production. The thermo-chemical pre-treatment of biomass was investigated. Statistical optimization was performed for medium formulation. Consolidated bioprocessing was attained using wild strain and consortium. Wild-type strain yielded maximum bioethanol of 8.91 g/L using pre-treated biomass.